Notes to Philosophy 167: Class 7 -- Galileo's Two New Sciences: Projectile Motion -- Part 6. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The Problem of Compound Impetus: Which Parabola -- Galileo's Solution for Compound Impetus -- Galileo's Determination of the Parabola.; Generally corresponds to the video segment: Class 7, Part 6.